Nourish the People The State Civilian Granary System in China, 1650-1850 - Will, Pierre-Etienne (Michigan Monographs in Chinese Studies, 2020)
The Qing state, driven by Confucian precepts of good government and urgent practical needs, committed vast resources to its granaries. Nourish the People traces the basic practices of this system, analyzes the organizational bases of its successes and failures, and examines variant practices in different regions. The volume concludes with an assessment of the granary system's social and economic impact and historical comparison with the food supply policies of other states.